American Time Use Survey (ATUS), 2006 ([Verlag nicht ermittelbar], 2008)
The American Time Use Survey (ATUS) collects information on how people living in the United States spend their time. Data collected in this study measured the amount of time that people spent doing various activities in 2006, such as paid work, child care, religious activities, volunteering, and socializing. Respondents were interviewed only once about how they spent their time on the previous day, where they were, and whom they were with. An Eating and Health (EH) module was introduced in January 2006, which included questions related to eating, meal preparation, and health, all of which were asked after completion of the ATUS questions. Part 1, Respondent and Activity Summary File, contains demographic information about respondents and a summary of the total number of minutes they spent doing each activity that day. Part 2, Roster File, contains information about household members and nonhousehold children under the age of 18. Part 3, Activity File, includes additional information on activities in which respondents participated, including the location of each activity and the total time spent on secondary child care. Part 4, Who File, includes data on who was present during each activity. Part 5, ATUS-CPS 2006 File, contains data on respondents and members of their household collected during their participation in the Current Population Survey (CPS). Parts 6 and 7 correspond to the 2006 Eating and Health (EH) Module. Parts 8-12 contain supplemental data files that can be used for further analysis of the data. Part 8, Case History File, contains information about the interview process. Part 9, Call History File, gives information about each call attempt. Part 10, Trips File, provides information about the number, duration, and purpose of overnight trips away from home for two or more nights in a row in a given reference month. Parts 11 and 12 contain base weights, replicate base weights, and replicate final weights for each case that was selected to be interviewed for the ATUS. Demographic variables include sex, age, race, ethnicity, education level, income, employment status, occupation, citizenship status, country of origin, and household composition.